Mastering Groovy programming : essential techniques for working with Spock, Spring, functional programming, and RESTful web services - Kousen, Kenneth A.; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Learn advanced techniques for working with the Groovy programming language. In this video workshop, presenter and Java consultant Ken Kousen shows you how to create RESTful web services, conduct Unit Tests, apply Groovy's functional programming features, and use Java's Spring Framework in conjunction with this JVM language. These courses demonstrate the many advantages of adding Groovy to existing projects written in Java and other object-oriented languages."--Resource description page.
Title from title screen.
Presenter, Ken Kousen.
Keywords: Groovy (Computer program language); Functional programming (Computer science); Electronic books